Environmental and Household Risk Factors Associated with Dengue Transmission: A Case–Control Study in Nakhon Nayok Province, Thailand - Jitjira Chaiyarit; Prat Intarasaksit (Journal of Epidemiology and Health Science, 2025)
Background: Dengue fever poses an escalating public health challenge in Thailand, with incidence rates rising steadily in recent years. Transmitted primarily by Aedes mosquitoes, dengue exerts a considerable health burden, particularly in vulnerable communities. Objective: This case–control study aimed to identify environmental health determinants associated with dengue transmission in Moo 4 (Ban Dongkha), Ko Pho Subdistrict, Pak Phli District, Nakhon Nayok Province. Methods: A total of 44 households were surveyed, including 4 households with confirmed dengue cases (cases) and 40 without any history of infection (controls), using a structured questionnaire developed by the research team. Descriptive statistics and Fisher’s Exact Test were applied to explore associations.Results: Although no statistically significant differences were observed between the two groups (p > 0.05), descriptive trends indicated that case households were more likely to have non-concrete housing, lack window or door screening, and exhibit higher densities of Aedes larvae. Knowledge, attitudes, and practices (KAP) related to dengue prevention were comparable across both groups.Conclusion: These findings suggest that structural and environmental conditions may play a more critical role in dengue transmission than individual knowledge or behavior. The study underscores the need for targeted interventions, including the installation of window screens and elimination of stagnant water, to reduce mosquito breeding and protect at-risk communities. Keywords: Dengue fever, Epidemic, Environmental health factors, Case–control study, Thailand